The Effect of Procrastination and Goal Orientation on Academic Dishonesty Moderated by Self-Efficacy in Postgraduate - Isna Mutmainah (‎‎‎TAZKIYA Journal of Psychology, 2023)
This unethical behavior occurs because of the mindset of each individual, if the individual thinks everyone is cheating, then they will tend to cheat. This study aims to see the effect of procrastination and goal orientation on academic dishonesty in post-graduate moderated by self-efficacy. The scale used for the data collection is the academic dishonesty scale by Bashir & Bala, the self-efficacy scale by Schwarzer & Jerusalem, the procrastination scale by Chun Chu & Choi, and the goal orientation scale by Button et al. The sampling technique used is nonprobability sampling with accidental sampling, which uses a Google form with a sample of 212. The construct validity test in this study is confirmatory factor analysis (CFA), while the hypothesis test uses moderated regression analysis (MRA). The results show a significant effect of self-efficacy, procrastination, and goal orientation (learning goal orientation and performance goal orientation) on academic dishonesty, and there is a significant effect of procrastination and goal orientation (learning goal orientation and performance goal orientation) on academic dishonesty moderated by self-efficacy. There is a significant effect of procrastination on academic dishonesty moderated by self-efficacy, there is an insignificant effect of learning goal orientation on academic dishonesty moderated by self-efficacy, and there is an insignificant effect of performance goal orientation on academic dishonesty moderated by self-efficacy. Further research can examine other variables impacting academic dishonesty, such as self-esteem, religiosity, and social support.